What body is that? The city and the real in the short story A unha encravada e o esmalte (2016), by Allan da Rosa - Santini, Juliana [UNESP] (Univ Fed Rio De Janeiro, Fac Letras, 2021)
This article discusses the forms of realism in contemporary Brazilian fiction and proposes an analysis of the short story A unha encravada e o esmalte, by Allan da Rosa, observing how the fragmentation of the human body acts in the representation of the city and its inequalities taking into consideration the marches that took place throughout Brazil in June 2013. The analysis starts from the hypothesis that the short story assumes, in the terms proposed by Tania Pellegrini (2018), a realistic posture sustained in a critical position that promotes an in-depth representation from the social constitution, making uses of aesthetic resources based not in the narration of facts or in the description of spaces, but in capturing the way in which each human body relates to space and other bodies. In this regard, the analysis carried out here highlights the deformation of the human body as a central instrument in the composition of the narrative, projecting itself on the representation of the city and on the social structures that comprise it as a fragmented and unequal body.
Keywords: Representation; Realism; Contemporary fiction; Allan da Rosa